(untitled) (Academicia Globe: Inderscience Research, 2022)
The organization and operation of horizontal or vertical management systems integrated into tourism enterprises or tourist complexes offering domestic tourism services in areas with tourism potential may pose a number of threats to competition in the management process. owner. This is because the risks that may arise in the process of carrying out tourism activities require a certain additional financial and resource costs for the tourism enterprise or system, which may pose a risk of crisis for the tourism enterprise.